Improved parameterization of the quantum harmonic oscillator model based on localized wannier functions to describe Van der Waals interactions in density functional theory - Partovi-Azar, Pouya; Berg, Matthias; Sanna, Simone; Kühne, Thomas D. (International Journal of Quantum Chemistry, 2016)
Recently, the quantum harmonic oscillator model has been combined with maximally localized Wannier functions to account for long-range dispersion interactions in density functional theory calculations (Silvestrelli, J. Chem. Phys. 2013, 139, 054106). Here, we present a new, improved set of values for the three parameters involved in this scheme. To test the new parameter set we have computed the potential energy curves for various systems, including an isolated Ar2 dimer, two N2 dimers interacting within different configurations, and a water molecule physisorbed on pristine graphene. While the original set of parameters generally overestimates the interaction energies and underestimates the equilibrium distances, the new parameterization substantially improves the agreement with experimental and theoretical reference values. © 2016 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2023-03-20
Keywords: density functional theory; quantum harmonic oscillator; Van der Waals interactions; Wannier orbitals